Variabilitas Genetik dan Heritabilitas Karakter Agronomi Galur-Galur Sawi (Brassica juncea L.): Variabilitas Genetik dan Heritabilitas Karakter Agronomi Galur-Galur Sawi (Brassica juncea L.) - Raihan Fadhil Muhammad; Budi Waluyo (Universitas Bangka Belitung, 2019)
The objective of this research was study genetic variability, heritability, and select the appearance of superior agronomic character genotypes in 57 Indian mustard for use in raw materials of consumption and industrial. This research was conducted at Seed Bank and Nursery, Agrotechno Park Brawijaya University, Jatikerto Village, Malang Regency in December 2018 - April 2019. The method used for this research was an augmented design. The treatment given was 60 genotypes of Indian mustard which consisted of 57 tested genotypes and 3 varieties as checks. The tested genotype will be spread into 5 blocks, while the three varieties of checks will be planted on each block, so there are 72 experimental units. The observation variables of agronomic characters consisted of 15 qualitative characters and 24 quantitative characters. Wide variability is found in the character of seeds per pod, number of pods per plant, and fresh weight. High heritability was found in the character of cotyledons, number of leaf consumption, fresh weight, age of seed harvest, number of pods per plant, length of pods, width of pods, and number of seeds per pod. There are Indian mustard which have superior characteristics for raw materials of consumption and industry.